Epidemiological profile and clinical outcome of patients hospitalized with COVID-19 at a University Hospital in Campo Grande - MS (Research, Society and Development, 2022)
Objective: to research the sociodemographic characteristics, presence of comorbidities, clinical management strategies and their relationship with outcome (death/discharge) of patients hospitalized in the Intensive Care Unit for COVID-19 at HUMAP-MS from February 2020 to September 2020. 2021. Methodology: observational, descriptive, cross-sectional and retrospective epidemiological study, with a quantitative approach to collection, carried out through the analysis of physical/digital medical records of patients admitted to the COVID-19 HUMAP-MS, located in Campo Grande - MS, in period from February 2020 to September 2021. Results: 172 patients participated in the study, divided into two groups, according to the observed clinical outcome, namely: Death Group (n=96) and Hospital Discharge Group (n=76) . Comparing the two groups studied, the death group had a higher mean age (p=0.0001), a higher prevalence of comorbidities (p=0.0038), a greater need for orotracheal intubation (p=0.0026), and a greater need to use NMB (p=0.0409). Individuals over 60 years of age had a 58% increased risk of death. The hospital discharge group had a greater number of days of hospitalization (p=0.0007). Conclusion: In the sample studied, mean age, presence of comorbidities, need for intubation and use of NMB were prevailing factors in individuals who evolved with the clinical outcome of death as a result of COVID-19 infection.